2017
DOI: 10.1371/journal.pone.0185850
|View full text |Cite
|
Sign up to set email alerts
|

Pleural effusion biomarkers and computed tomography findings in diagnosing malignant pleural mesothelioma: A retrospective study in a single center

Abstract: In this study, we aimed to examine the clinical value of the pleural effusion (PE) biomarkers, soluble mesothelin-related peptide (SMRP), cytokeratin 19 fragment (CYFRA 21–1) and carcinoembryonic antigen (CEA), and the utility of combining chest computed tomography (CT) findings with these biomarkers, in diagnosing malignant pleural mesothelioma (MPM). We conducted a retrospective cohort study in a single center. Consecutive patients with undiagnosed pleural effusions who underwent PE analysis between Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Ultimately, 13 studies met our eligibility criteria were included in this meta-analysis, involving a total of 3359 patients. [1628] One study had 2 best diagnostic performances, which were considered 2 independent studies. [17]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultimately, 13 studies met our eligibility criteria were included in this meta-analysis, involving a total of 3359 patients. [1628] One study had 2 best diagnostic performances, which were considered 2 independent studies. [17]…”
Section: Resultsmentioning
confidence: 99%
“…Most studies [1726] used histopathologic immunochemistry method as diagnostic criteria for MPM, only 3 studies [16,27,28] used PE cytology with biopsy histology as diagnostic criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…58 Our pleural effusion segmentations are likely to be useful for investigating two questions surrounding a CT or PET/CT finding of pleural effusion: (a) the prognostic significance of pleural effusion in various cancer types, 59 and (b) the capacity of CT to discriminate between benign and malignant effusions. [60][61][62][63] Regarding the first question, Ryu et al 59 showed that in small cell lung cancer with stage I-III disease, the presence of even minimal pleural effusion confers an increased risk of death. Investigating the prognostic relationship of pleural effusion presence in other cancer types would presumably be facilitated by deep learning pleural effusion segmentation algorithms, such as might be trained with datasets like ours.…”
Section: Discussionmentioning
confidence: 99%
“…Our pleural effusion segmentations are likely to be useful for investigating two questions surrounding a CT or PET/CT finding of pleural effusion: (a) the prognostic significance of pleural effusion in various cancer types, 59 and (b) the capacity of CT to discriminate between benign and malignant effusions 60–63 . Regarding the first question, Ryu et al 59 showed that in small cell lung cancer with stage I–III disease, the presence of even minimal pleural effusion confers an increased risk of death.…”
Section: Discussionmentioning
confidence: 99%